Establishment of performance parameters for the Qubit™ 1X dsDNA HS Assay for use in forensic genetics casework - Adele Lauren Kaleigh Naidoo; Donna-Lee Pamela Martin; Laura Jane Heathfield (Forensic Science International: Reports)
Next generation sequencing is being more regularly used in forensic casework, particularly for post-mortem genetic analyses in sudden unexpected death cases. Accurate quantification of DNA and associated sequencing libraries is essential, however, no validation studies have been published on the recommended fluorometric quantification methods. The aim of this study was to optimise and internally validate the Qubit™ 1X dsDNA HS Assay Kit on the Qubit™ 4 Fluorometer as part of a molecular autopsy workflow for forensic applications. An optimised working solution equilibration period, sample incubation time and dilution medium were established. The optimised workflow was then used to assess the DNA concentration of control Lambda DNA, DNA extracted from forensic samples and sequencing libraries. The accuracy, precision, dynamic range, and sensitivity were established in accordance with ISO 17025 standards. All parameters met the manufacturer’s criteria of acceptance except for the precision of measurements for samples with DNA concentrations greater than or equal to 0.5 ng/µl, which were expected to have less than 1 % CV. The precision of the measurements (1.2–2.44 % CV), however, was deemed acceptable for our laboratory, as downstream DNA sequencing results surpassed quality thresholds. Additionally, precision between operators was poor. This study has advanced our progression towards implementing a molecular autopsy sequencing workflow in South Africa and provides the first performance parameters for the Qubit™ 1X dsDNA HS Assay Kit which may be useful for other laboratories.